Analysis of the Basic Futsal Technical Skill Level of Azzhazel Club Athletes in Semarang City - Fadhil Faadihilah Novanto; Gustiana Mega Anggita; Lina Lina Farda Andani (Universitas Negeri Semarang, 2026)
The purpose of this study was to determine the level of basic futsal technical skills of the Azzhazel Club athletes in Semarang City. The method used was a survey with test and measurement techniques. Through tests and measurements, objective data will be obtained. The subjects of this study were 20 athletes from the Azzhazel Club in Semarang City. Data collection was carried out through observation and tests. Data analysis was carried out descriptively quantitatively. The results of this study were declared